Characteristics of food supply for benthos-eating fish in the lower Don - Lyubov A. Zhivoglyadova; Lyudmila N. Frolenko (Известия ТИНРО)
New data are presented on qualitative and quantitative composition of forage benthos obtained in hydrobiological surveys in the lower Don River in 2016. The area from Semikarakosk to the mouth (193 km), including the Don estuary, was surveyed. The benthos was sampled by Petersen dredge of 0.025 m2; in total 60 samples were processed, with some replicate ones. Mollusca was the main group of the forage benthos both in May, June, and September, mostly due to high abundance of zebra mussels. The biomass of forage mollusks varied in the range of 1.3-104.3 g/m2, with the maximum in September after settling of D. polymorpha and D. bugensis juveniles. The biomass of “soft” forage benthos (mainly oligochaetes and chironomids) ranged from 6.3 to 12.6 g/m2. By quantitative abundance of benthic fauna, the feeding capacity of the lower Don is assessed as high.